Management of sub-national demands: the Chittagong Hill tracts peace treaty of Bangladesh - Hossain, Ishtiaq (Pakistan American Foundation, 2002)
This paper, first of all, looks into some of the issues dividing the political elite of Bangladesh. This is done to emphasise the argument that the mere presence of institutions does not augur well for the effective functioning of the democratic system in a developing country like Bangladesh. Then this paper will analyse the controversy over the CHT Peace Treaty. This is done to illustrate the point that without a national consensus the management of sub-national demands remains problematic for a Third World country like Bangladesh.